Asymmetric impacts of exchange rate and petroleum pump price on economic welfare in Nigeria - Abere, Sesan Sunday (Economic Journal of Emerging Markets, 2025)
Purpose — This study examines the asymmetric effects of exchange rate fluctuations and petroleum pump prices on economic welfare in Nigeria. While previous research examined these shocks in isolation, this study jointly evaluates their short-run and long-run effects, thereby addressing a key gap in the literature.Methods — The study employs the Nonlinear Autoregressive Distributed Lag (NARDL) model to analyse time-series data from 1970 to 2023.Findings — Exchange rate depreciations and petroleum price increases have larger and lasting welfare losses than the short-run benefits of appreciations and price declines. In the long run, these shocks can be turned into potential welfare benefits through structural changes and redistribution of the budget. Inflation, unemployment, subsidies and international oil prices further mediate outcomes.Implications — Policymakers should strike a balance between short-term household protection and longer-term structural changes. With the complete removal of petroleum subsidies in Nigeria in May 2023, the focus should shift to special transfers, social security, and compensation to mitigate welfare losses. Exchange rate stability, fiscal discipline and diversification are equally essential for enhancing long-term welfare.Originality — This study advances understanding of welfare by concurrently examining the asymmetries of exchange rates and petroleum pump prices, thereby moving beyond the single-shock approach.